Imitation reinforcement network-concrete structure reinforced antibacterial-bone repair composite gel material and preparation method thereof

By introducing PLGA fiber/silver wire 3D stereoscopic network and HA filler into bone repair hydrogel, a rebar network-concrete structure is formed, which solves the problems of poor mechanical strength of bone repair materials and insignificant antibacterial osteogenic activity, and achieves bone Efficiency, safety and customization of defect repair.

CN119424763APending Publication Date: 2025-02-14ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302246.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing bone repair hydrogels have poor mechanical strength, and their antibacterial and osteogenic activities are not significant, making it difficult to meet the high mechanical properties and anti-infection needs of bone defect repair.

Method used

The antibacterial-bone repair composite gel material enhanced by imitation steel bar network-concrete structure is adopted. By introducing PLGA fiber/silver wire 3D stereo network and HA filler, an imitation steel bar network-concrete structure is formed, combining fiber braiding, in-situ casting, and ultrasonic detachment. Through bubble and UV curing processes, bone repair materials with excellent mechanical properties and anti-infection properties were prepared.

Benefits of technology

It has achieved the improvement of the mechanical properties of the hydrogel, has high biocompatibility, degradability, anti-infection performance and bone-promoting function, and is suitable for efficient repair of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424763A_ABST
    Figure CN119424763A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial-bone repair composite gel material based on reinforcing steel bar network simulation-concrete structure enhancement and a preparation method thereof. The method comprises the following specific steps: 1) constructing a fiber fixing frame, and weaving polylactic acid fibers and silver wires on the fiber fixing frame to obtain a 3D fiber network frame; 2) putting the fiber network frame into a mold; (3) preparing a methylacryloylated hyaluronic acid / methylacryloylated gelatin mixed solution doped with hydroxyapatite, pouring the methylacryloylated hyaluronic acid / methylacryloylated gelatin mixed solution into the mold, and then carrying out ultrasonic defoaming; and (4) performing in-situ curing on the network frame and the mixed solution in the mold by using a UV light source to form an imitated reinforcement network-concrete structure, performing freezing demolding, cutting by using a cylindrical cutter, performing freezing removal, and performing sterilization to obtain the antibacterial-bone repair composite gel material. According to the invention, matrix enhancement is realized through a simulated reinforcement network-concrete structure, and the material is endowed with antibacterial and osteogenic properties by using silver wires and hyaluronic acid (HA).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation technology of a bone repair material, and in particular to an antibacterial-bone repair composite gel material with reinforced imitation steel network-concrete structure and a preparation method thereof. Background Art

[0002] Bone defect is a very common orthopedic disease, mainly caused by accidents, accidents, surgeries, etc. If bone defects are not treated properly, it will cause a series of complications such as septic shock, osteomyelitis, and osteonecrosis, which may cause patients to have difficulty in moving, or even cause patients to be disabled or even die. Therefore, how to achieve better bone defect treatment effects is currently a research hotspot in this field.

[0003] Clinical treatments for bone defects mainly include implanting autologous bone or artificial bone, but the above materials have problems such as limited sources, secondary damage, or insignificant biological activity. With the development of tissue engineering technology in recent years, bone tissue engineering materials have gradually emerged. Hydrogels, as an important application form of bone tissue engineering, have been widely studied, but the mechanical strength of natural polymers is inherently defective, and cross-linking agents can only be used in trace amounts due to toxicity restrictions. Therefore, how to improve the mechanical properties of biomedical hydrogels has always been a technical problem that has troubled everyone. At the same time, the bone defect repair cycle is long, and bone defects caused by reasons such as car accidents and accidents are often accompanied by a large number of pollutants, which makes the affected area very susceptible to infection. Once bone infection occurs, its long-lasting characteristics will bring huge psychological and physiological burdens to patients. Therefore, for new bone repair materials, not only high biocompatibility, biodegradability, and osteogenic properties are required, but also extremely high requirements are placed on their mechanical properties and anti-infection properties.

[0004] In view of the above problems, the present invention proposes an antibacterial-bone repair composite gel material reinforced by imitating a steel network-concrete structure and a preparation method thereof. By introducing a physical PLGA fiber / silver wire 3D network and doping HA filler in the hydrogel matrix, a steel network-concrete structure is formed to enhance the hydrogel; at the same time, the introduction of silver wire and HA gives the material excellent anti-infection and bone-promoting functions. The use of the above raw materials and the design of the structure provide a new strategy for the innovative upgrading of new functional bone repair materials. Summary of the invention

[0005] The purpose of the present invention is to provide an antibacterial-bone repair composite gel material and a preparation method thereof that simulates the reinforced steel network-concrete structure to address the problems of poor mechanical strength, insignificant antibacterial and osteogenic activity of traditional bone repair hydrogels. The novel gel material achieves matrix reinforcement by imitating the reinforced steel network-concrete network, and uses silver wire and HA to give the material antibacterial and osteogenic properties, which is of great significance for bone defect repair.

[0006] The present invention is implemented by the following technical solution, and the specific steps are as follows:

[0007] A method for preparing an antibacterial-bone repair composite gel material reinforced with a steel network-concrete structure, comprising the following steps:

[0008] 1) constructing a fiber fixing frame, using polylactic acid (PLGA) fibers and silver wires to weave a 3D fiber network on the fiber fixing frame to obtain a 3D fiber network frame;

[0009] 2) placing the 3D fiber network frame into a mold with an opening at the upper end;

[0010] 3) preparing a mixed solution of methacryloyl hyaluronic acid (HAMA) / methacryloyl gelatin (GelMA) doped with hydroxyapatite, pouring the mixed solution into the mold, and then performing ultrasonic degassing;

[0011] 4) using a UV light source to in-situ solidify the 3D fiber network framework and the mixed solution in the mold to form a steel network-concrete structure, and after freeze demolding, using a cylindrical cutter to cut and freeze remove, retaining the part inside the cylindrical cutter, and obtaining an antibacterial-bone repair composite gel material after sterilization.

[0012] Furthermore, the fiber fixing frame in step 1) is a "well"-shaped round rod array, the round rods have a diameter of 1-2 mm, a height of 1-10 cm, and the intervals between the round rods are 0.3-1 cm.

[0013] Furthermore, the diameter of the cylindrical cutter is equal to the diameter of the outermost circumscribed circle of the "well" shaped round rod array, and the cutting is performed along the axis direction of the round rod. The freezing removal temperature is -20 to -80°C to prevent the gel surface from breaking.

[0014] Furthermore, in step 1), the PLGA fibers and the silver wires are connected to each row or column of adjacent round rods in a winding manner to form a 3D fiber network, and the PLGA fibers and the silver wires are arranged at an interval of 0.3-1 cm above and below.

[0015] Furthermore, in step 2), the size of the mold is larger than the fiber fixing frame, and the material is PMMA or PET, with a thickness of about 2-3 mm.

[0016] Further, in step 3), the mixed solution contains a photoinitiator, the hydroxyapatite particle size is about 100-200nm, and the concentration is 0.5-5wt%;

[0017] The HAMA substitution degree is 30-60% and the concentration is 5-15wt%;

[0018] The degree of GelMA substitution is 30-60% and the concentration is 5-15wt%;

[0019] The photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, and the concentration is 0.25-0.5 wt %.

[0020] Furthermore, in step 3), the mixed solution is prepared under light-proof conditions, a temperature of 60-70° C., and ultrasound-assisted dispersion;

[0021] During the ultrasonic degassing process, the ultrasonic power is 180-200W and the ultrasonic time is 15-40min.

[0022] Furthermore, in step 4), the UV light source is a hood-type UV light source with a volume 3-5 times that of the fiber frame, a wavelength of 405 nm, a power of 20-30 W, and a curing time of 10-30 min.

[0023] An antibacterial-bone repair composite gel material reinforced by imitating a steel network-concrete structure is obtained by using any of the above-mentioned preparation methods.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] 1) The present invention uses PLGA fiber, silver wire, HA, HAMA, GelMA and the like as raw materials, and combines fiber weaving, in-situ casting, ultrasonic degassing, UV curing, cutting and other combined processes to prepare an antibacterial-bone repair composite gel material that imitates a steel network-concrete structure reinforcement. The above raw material selection and process combination are original to the present invention.

[0026] 2) In the present invention, a "well"-shaped round rod array is designed, and a 3D fiber network is formed by weaving back and forth between adjacent round rods in each row or column in an eight-shaped manner to obtain the desired 3D fiber network. The above-mentioned woven mold frame and the related fiber weaving method are designed based on the desired 3D fiber network structure, realizing the new application of simple devices and old processes, and providing the possibility of forming an imitation steel network-concrete structure. At the same time, the subsequent use of simple in-situ casting, ultrasonic degassing and UV curing can easily obtain the desired imitation steel network-concrete reinforced bone defect repair material. The characteristics of the fiber network being fixed and complex in structure are cleverly avoided, and nanofillers and polymer matrices are introduced between the networks. Finally, the gel is cut with a cutter to obtain a bone defect repair material of the desired shape and size. Although the above-mentioned single process has been widely used, here the applicant combines the actual scene and needs of the preparation of this material, carefully designs and coordinates the organic combination of the above-mentioned processes, and the application of technology is collaborative and innovative.

[0027] 3) The present invention designs a new steel bar network-concrete structure to provide mechanical reinforcement for bone defect repair materials. The steel bar network is a 3D fiber network woven by PLGA fibers and silver wires, and its shape is highly similar to the steel frame structure formed by the combination of steel bars when pouring the wall structure of a construction site in life; on the other hand, HA is used to analogize the gravel in concrete, and HAMA / GelMA is mixed to analogize the cement and sand in concrete, and the above together realize the simulation of concrete. The HAMA / GelMA solution of the composite HA is further poured between the three-dimensional fiber networks by a pouring method, and the desired steel bar network-concrete structure is formed after solidification. Its structure is highly similar and effectively realizes the enhancement effect of the hydrogel.

[0028] 4) The composite gel material in the present invention has high biocompatibility, degradability, high mechanical properties, anti-infection properties and osteogenic properties. The high biocompatibility and degradability are derived from the selection of raw materials. The raw materials in the present invention are mainly HAMA, GelMA, PLGA and HA, all of which are degradable and non-biotoxic. Secondly, the steel network-concrete structure formed by the fiber network and nanofillers gives the hydraulic gel excellent mechanical properties. At the same time, a small amount of silver wire doped in the fiber network and the HA filler mixed in the GelMA matrix provide anti-infection and osteogenic properties, respectively. Silver wire can kill bacteria in the affected area by contacting and releasing silver ions, thereby achieving the purpose of anti-infection, and HA can release phosphate ions and calcium ions through degradation to enhance the effect of bone repair. It is the synergy of the above-mentioned raw materials and structures that gives the material such a comprehensive function and achieves the effect of efficient repair of bone defects.

[0029] 5) The fiber woven frame structure, casting mold, etc. used in the present invention are flexible and adjustable, and can be customized according to the size of the bone defect area to produce the required antibacterial-bone repair composite gel material reinforced with a steel network-concrete structure. It is efficient and convenient, the technology is universal, and the material is customizable. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the preparation process of the antibacterial-bone repair composite gel material reinforced with a steel bar network-concrete structure according to an embodiment of the present invention;

[0031] Figure 2 This is a silver ion release curve of an antibacterial-bone repair composite gel material reinforced with a steel network-concrete structure according to an embodiment of the present invention (Example 1). DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below with reference to the accompanying drawings and specific examples. Figure 1 Comparative Example 1:

[0033] 1) Prepare a mixed solution of HAMA (substitution degree 60%) / GelMA (substitution degree 60%) doped with hydroxyapatite (particle size of about 100-200nm), wherein the concentration of HAMA is 10wt%, the concentration of GelMA is 10wt%, the photoinitiator is LAP, the concentration is 0.4wt%, and the solvent is PBS. Mix the above materials under light-proof conditions, transfer to a 60°C water bath and heat to dissolve completely, then add hydroxyapatite with a concentration of 2.5wt%, mix and disperse evenly with ultrasound assistance. Then pour the above solution into the mold and degas by ultrasound (power 180W, ultrasound time 20min);

[0034] 2) Using a hood-type UV light source (the volume of the hood-type UV light source is 3 times that of the mold, the wavelength is 405 nm, the power is 20 W, and the curing time is 15 min) to in-situ cure the above solution, and then sterilize it to obtain a gel material.

[0035] The extract was prepared using the above-mentioned gel material, and the CCK-8 results showed that the cell survival rate was about 92.6% after co-culture with bone marrow mesenchymal stem cells (BMSCs) for 7 days; the hydrogel in this example broke when bent once, and the compressive strength was about 235 kPa; the above-mentioned material (1 cm diameter disc) was used to conduct an in vitro inhibition zone experiment, and the results showed that no inhibition zone was generated.

[0036] Embodiment 1:

[0037] 1) First, construct a "well"-shaped fiber fixing frame (using 10 round rods to form an array frame, the array arrangement is shown in the attached Figure 1 , the diameter of the round rod is 1 mm, the height is 2 cm, and the interval between the round rods is 0.5 cm), PLGA fibers are woven back and forth between adjacent round rods in each row or column in a figure eight manner to form a 3D fiber network framework, and silver wires are doped in the fiber network framework at an interval of 0.3 cm from top to bottom;

[0038] 2) placing the 3D fiber network frame in a PMMA transparent mold with an upper opening (about 1.5 cm in diameter and 2 mm in wall thickness);

[0039] 3) Prepare a mixed solution of HAMA (substitution degree 60%) / GelMA (substitution degree 60%) doped with hydroxyapatite (particle size of about 100-200nm), wherein the concentration of HAMA is 10wt%, the concentration of GelMA is 10wt%, the photoinitiator is LAP, the concentration is 0.4wt%, and the solvent is PBS. Mix the above materials under light-proof conditions, transfer to a 60°C water bath and heat to dissolve completely, then add hydroxyapatite with a concentration of 2.5wt%, mix and disperse evenly with ultrasound. Then pour the above mixed solution into the mold and degas by ultrasound (power 180W, ultrasound time 20min);

[0040] 4) Use a hood-type UV light source (the volume of the hood-type UV light source is 3 times that of the fiber frame, the wavelength is 405nm, the power is 20W, and the curing time is 15min) to in-situ cure the 3D fiber network frame and the mixed solution in the mold to form an imitation steel network-concrete structure. After freeze demolding, use a cylindrical cutter (the diameter of the cutter is equal to the diameter of the outermost circumscribed circle of the "well"-shaped round rod array) to cut from top to bottom. After cutting, freeze-release at -80°C to prevent the gel surface from breaking. The part inside the frame is retained, that is, the part inside the cylindrical cutter tube is retained, and the antibacterial-bone repair composite gel material is obtained after sterilization.

[0041] Compared with Comparative Example 1, this embodiment adds the introduction of a three-dimensional fiber network. The extract was prepared using the above gel material, and the CCK-8 results showed that the cell survival rate was about 90.2% after co-culture with BMSCs for 7 days; the hydrogel in this embodiment could withstand more than 15 bendings without breaking, and the compression strength was about 297kPa; the above material (1cm diameter disc) was used to conduct an in vitro antibacterial zone experiment, and the results showed that the antibacterial zone area was about 2.87cm 2 ,like Figure 2 This is the silver ion release curve of the antibacterial-bone repair composite gel material reinforced with the steel network-concrete structure of this embodiment.

[0042] Embodiment 2:

[0043] 1) First, a "well"-shaped fiber fixing frame was constructed (21 round rods were used to form an array frame, the round rods had a diameter of 1 mm, a height of 2 cm, and a spacing of 0.3 cm between the round rods), and PLGA fibers were used to weave back and forth between adjacent round rods in each row or column in an "eight" manner to form a 3D fiber network frame, and silver wires were doped in the fiber network frame at a distance of 0.3 cm from top to bottom;

[0044] 2) placing the 3D fiber network frame in a PMMA transparent mold with an upper opening (about 1.5 cm in diameter and 2 mm in wall thickness);

[0045] 3) Prepare a mixed solution of HAMA (substitution degree 60%) / GelMA (substitution degree 60%) doped with hydroxyapatite (particle size of about 100-200nm), wherein the concentration of HAMA is 10wt%, the concentration of GelMA is 10wt%, the photoinitiator is LAP, the concentration is 0.4wt%, and the solvent is PBS. Mix the above materials under light-proof conditions, transfer to a 60°C water bath and heat to dissolve completely, then add hydroxyapatite with a concentration of 2.5wt%, mix and disperse evenly with ultrasound. Then pour the above mixed solution into the mold and degas by ultrasound (power 180W, ultrasound time 20min);

[0046] 4) Use a hood-type UV light source (the volume of the hood-type UV light source is 3 times that of the fiber frame, the wavelength is 405nm, the power is 20W, and the curing time is 15min) to in-situ cure the 3D fiber network frame and the mixed solution in the mold to form an imitation steel network-concrete structure. After freeze demolding, use a cylindrical cutter (the diameter of the cutter is equal to the diameter of the outermost circumscribed circle of the "well"-shaped round rod array) to cut from top to bottom. After cutting, freeze-release at -80°C to prevent the gel surface from breaking. The part inside the frame is retained, that is, the part inside the cylindrical cutter tube is retained, and the antibacterial-bone repair composite gel material is obtained after sterilization.

[0047] Compared with Example 1, this example improves the density of the "rebar network", that is, the density of the PLGA three-dimensional fiber network. The extract was prepared using the above gel material, and the CCK-8 results showed that the cell survival rate was about 89.1% after co-culture with BMSCs for 7 days; the hydrogel in this example can withstand more than 20 bends without breaking, and the compression strength is about 324kPa; the above material (1cm diameter disc) was used to perform an in vitro antibacterial zone experiment, and the results showed that the antibacterial zone area was about 3.22cm 2 .

[0048] Embodiment 3:

[0049] 1) First, construct a "well"-shaped fiber fixing frame (using 10 round rods to form an array frame, the array arrangement is shown in the attached Figure 1 , the diameter of the round rod is 1 mm, the height is 2 cm, and the interval between the round rods is 0.5 cm), PLGA fibers are woven back and forth between adjacent round rods in each row or column in a figure eight manner to form a 3D fiber network framework, and silver wires are doped in the fiber network framework at an interval of 0.3 cm from top to bottom;

[0050] 2) placing the 3D fiber network frame in a PMMA transparent mold with an upper opening (about 1.5 cm in diameter and 2 mm in wall thickness);

[0051] 3) Prepare a mixed solution of HAMA (substitution degree 60%) / GelMA (substitution degree 60%) doped with hydroxyapatite (particle size of about 100-200nm), wherein the concentration of HAMA is 5wt%, the concentration of GelMA is 5wt%, the photoinitiator is LAP, the concentration is 0.25wt%, and the solvent is PBS. Mix the above materials under light-proof conditions, transfer to a 60°C water bath and heat to dissolve completely, then add 0.5wt% hydroxyapatite, mix and disperse evenly with ultrasound. Then pour the above mixed solution into the mold and degas by ultrasound (power 180W, ultrasound time 20min);

[0052] 4) Use a hood-type UV light source (the volume of the hood-type UV light source is 3 times that of the fiber frame, the wavelength is 405nm, the power is 20W, and the curing time is 15min) to in-situ cure the 3D fiber network frame and the mixed solution in the mold to form an imitation steel network-concrete structure. After freeze demolding, use a cylindrical cutter (the diameter of the cutter is equal to the diameter of the outermost circumscribed circle of the "well"-shaped round rod array) to cut from top to bottom. After cutting, freeze-release at -80°C to prevent the gel surface from breaking. The part inside the frame is retained, that is, the part inside the cylindrical cutter tube is retained, and the antibacterial-bone repair composite gel material is obtained after sterilization.

[0053] Compared with Example 1, this example reduces the density of the "concrete" structure, that is, reduces the concentration of polymers and nanofillers in the polymer matrix. The extract was prepared using the above gel material, and the CCK-8 results showed that the cell survival rate was about 87.4% after 7 days of co-culture with BMSCs; the hydrogel in this example can withstand more than 5 bendings without breaking, and the compression strength is about 196kPa; the above material (1cm diameter disc) was used to conduct an in vitro antibacterial zone experiment, and the results showed that the antibacterial zone area was about 3.48cm 2 .

Claims

1. A method for preparing an antibacterial-bone repair composite gel material reinforced with a steel network-concrete structure, characterized in that: The following steps are involved: 1) constructing a fiber fixing frame, using polylactic acid (PLGA) fibers and silver wires to weave a 3D fiber network on the fiber fixing frame to obtain a 3D fiber network frame; 2) placing the 3D fiber network frame into a mold with an upper opening; 3) preparing a mixed solution of methacryloyl hyaluronic acid (HAMA) / methacryloyl gelatin (GelMA) doped with hydroxyapatite, pouring the mixed solution into the mold, and then performing ultrasonic degassing; 4) using a UV light source to in-situ solidify the 3D fiber network framework and the mixed solution in the mold to form a steel network-concrete structure, and after freeze demoulding, using a cylindrical cutter to cut and freeze remove, and after sterilization, obtaining an antibacterial-bone repair composite gel material.

2. The method for preparing the antibacterial-bone repair composite gel material reinforced with a steel network-concrete structure according to claim 1, characterized in that: The fiber fixing frame in step 1) is a "well"-shaped round rod array, the round rod diameter is 1-2mm, the height is 1-10cm, and the interval between the round rods is 0.3-1cm.

3. The method for preparing the antibacterial-bone repair composite gel material reinforced with imitation steel network-concrete structure according to claim 2, characterized in that: In step 4), during the cutting process with the cylindrical cutter, the diameter of the cylindrical cutter is equal to the diameter of the outermost circumscribed circle of the "well" shaped round rod array, and the cutting is carried out along the axis direction of the round rod. The freezing removal temperature is -20 to -80°C.

4. The method for preparing the antibacterial-bone repair composite gel material reinforced with a steel network-concrete structure according to claim 1, characterized in that: In step 1), during the weaving of the 3D fiber network, the PLGA fibers and the silver wires are connected to each row or column of adjacent round rods in a figure eight winding manner to form a 3D fiber network, and the PLGA fibers and the silver wires are arranged with an upper and lower interval of 0.3-1 cm.

5. The method for preparing the antibacterial-bone repair composite gel material reinforced with imitation steel network-concrete structure according to claim 1, characterized in that: In step 2), the size of the mold is larger than the fiber fixing frame, the material is PMMA or PET, and the thickness is about 2-3 mm.

6. The method for preparing the antibacterial-bone repair composite gel material reinforced with imitation steel network-concrete structure according to claim 1, characterized in that: In step 3), the mixed solution contains a photoinitiator, the hydroxyapatite particle size is about 100-200nm, the concentration is 0.5-5wt%; the HAMA substitution degree is 30-60%, the concentration is 5-15wt%; the GelMA substitution degree is 30-60%, the concentration is 5-15wt%; the photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, and the concentration is 0.25-0.5wt%.

7. The method for preparing the antibacterial-bone repair composite gel material reinforced with imitation steel network-concrete structure according to claim 1, characterized in that: In step 3), the mixed solution is prepared under light-proof conditions, a temperature of 60-70° C., and ultrasound-assisted dispersion; During the ultrasonic degassing process, the ultrasonic power is 180-200W and the ultrasonic time is 15-40min.

8. The method for preparing the antibacterial-bone repair composite gel material reinforced with imitation steel network-concrete structure according to claim 1, characterized in that: In step 4), the UV light source is a hood-type UV light source with a volume 3-5 times that of the fiber frame, a wavelength of 405 nm, a power of 20-30 W, and a curing time of 10-30 min.

9. An antibacterial-bone repair composite gel material that simulates a reinforced steel network-concrete structure, characterized in that The method is adopted as claimed in any one of claims 1 to 8.